The significance of subculture among Malaysian teenagers in 2015-2016 / Nur Farhana Mohd Sukeri - Nur Farhana, Mohd Sukeri (Universiti Teknologi MARA, Perak, 2018)
Definition of subculture in Oxford English Dictionary is a cultural group within a larger culture, often having belief or interests at varience with those of larger culture. In addition, another definition of subculture which is centres on cultural substance and is hence stripped of its former connotations of youth, working-classness, collective resistance and devience. Subculture can be perceived as negative due to their nature of critism to the dominant societal standard. In this situation, subculture feels neglected by social standard and allows them to develop a sense of identity. Subculture can be identified through clothing, music such as skinhead and punk, fashion, argot and mannerism